2002
DOI: 10.7863/jum.2002.21.4.455
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Median Artery in the Carpal Tunnel

Abstract: Objective. To describe the ultrasonographic and color Doppler ultrasonographic findings in 2 patients with carpal tunnel syndrome associated with a persistent median artery and to report the frequency of this anatomic variation in healthy volunteers. Methods. Two patients with the clinical appearance of carpal tunnel syndrome and 100 wrists and distal forearms of 50 asymptomatic volunteers were examined with ultrasonography and color Doppler ultrasonography. The frequency and size of a persistent median artery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
1
6

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(30 citation statements)
references
References 25 publications
0
23
1
6
Order By: Relevance
“…Both magnetic resonance imaging (MRI) and ultrasonography are used to detect median nerve anomalies, and the use of ultrasonography and MRI to detect carpal tunnel has been recently reported 8-10. Ultrasonography is recognized as a useful imaging method to visualize internal body structures, including tendons, muscles, nerves, joints, vessels and internal organs for potential pathology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both magnetic resonance imaging (MRI) and ultrasonography are used to detect median nerve anomalies, and the use of ultrasonography and MRI to detect carpal tunnel has been recently reported 8-10. Ultrasonography is recognized as a useful imaging method to visualize internal body structures, including tendons, muscles, nerves, joints, vessels and internal organs for potential pathology.…”
Section: Discussionmentioning
confidence: 99%
“…The practice of dynamically examining the musculoskeletal system using ultrasound in real time is widely used. The use of sonography at high frequencies has been demonstrated to be a useful diagnostic tool in patients with CTS 10-12. The small structures of a bifid median nerve and the relationship of this structure to a persistent median artery can be observed more clearly using an 18-MHz high-frequency transducer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They conclude that a PMA has a superficial course close to the transverse carpal ligament; pre-operative diagnosis of this anatomic variation may be of clinical importance. [16]…”
Section: Discussionmentioning
confidence: 99%
“…Gassner et al ., in a study of 50 asymptomatic volunteers, found a persistent median artery in 16 of 100 (16%) wrists. In 10 of these 16 wrists, there was an associated high division or bifid nerve 13 . Wong et al .…”
Section: Discussionmentioning
confidence: 99%